Panic disorder and exercise avoidance - Muotri,Ricardo W. (2014)
Objectives: 1) To identify whether patients with panic disorder in general and those with the respiratory subtype in particular actively avoid exercise; 2) to investigate physiological differences in cardiopulmonary function parameters in patients with panic disorder in general, patients with the respiratory subtype of panic disorder, and healthy controls upon exercise challenge. Methods: Patients with panic disorder were classified as having either the respiratory or the non-respiratory subtype. Both groups were compared to controls in terms of exercise avoidance patterns and performance on cardiopulmonary exercise testing. Results: Patients with panic disorder exhibited higher exercise avoidance scores and worse performance on cardiopulmonary exercise testing as compared with controls. No differences were found between patients with the respiratory and non-respiratory subtypes. Conclusions: Exercise avoidance is present in panic disorder and is associated with poorer performance on cardiopulmonary exercise testing. These findings are not limited to patients with the respiratory subtype of the disorder.